Correction of the X-linked immunodeficiency phenotype by transgenic expression of human Bruton tyrosine kinase under the control of the class II major histocompatibility complex Ea locus control region - Drabek, Dubravka (The National Academy of Sciences of the USA, 1997)
Bruton tyrosine kinase (Btk) is essential for the development of pre-B cells to mature B cell stages. Btk-deficient mice manifest an X-linked immunodeficiency (xid) defect characterized by a reduction of peripheral IgM(low) IgD(high) B cells, a lack of peritoneal CD5(+) B cells, low serum levels of IgM and IgG3, and impaired responses to T cell independent type II (TI-II) antigens. We have generated transgenic mice in which expression of the human Btk gene is driven by the murine class II major histocompatibility complex Ea gene locus control region, which provides gene expression from the pre-B cell stage onwards. When these transgenic mice were mated onto a Btk(−) background, correction of the xid B cell defects was observed: B cells differentiated to mature IgM(low)IgD(high) stages, peritoneal CD5(+) B cells were present, and serum Ig levels and in vivo responses to TI-II antigens were in the normal ranges. A comparable rescue by transgenic Btk expression was also observed in heterozygous Btk(+/−) female mice in those B-lineage cells that were Btk-deficient as a result of X chromosome inactivation. These findings indicate that the Btk(−) phenotype in the mouse can be corrected by expression of human Btk from the pre-B cell stage onwards.